The economics of private digital currency - Gerald P. Dwywer (LUISS Guido Carli, Department of Economics and Business, Arcelli Centre for Monetary and Financial Studies, 2014)
Recent innovations have made it feasible to transfer private digital currency without the intervention of an institution. A digital currency must prevent users from spending their balances more than once, which is easier said than done with purely digital currencies. Current digital currencies such as Bitcoin use peer-to-peer networks and open-source software to stop double spending and create finality of transactions. This paper explains how the use of these technologies and limitation of the quantity produced can be equilibrium strategies in which a digital currency has a positive value. This paper also summarizes the rise of 24/7 trading on a computerized market in Bitcoin, a remarkable innovation in financial markets. I conclude that exchanges of foreign currency may be the obvious way in which use of digital currencies can become widespread.
Keywords: 330